The Effects of the Use of Striker Replacement Workers in Canada: An Analysis of Four Cases - Singh, Parbudyal; Zinni, Deborah M.; Jain, Harish C. (Labor Studies Journal, 2005)
The use of striker replacements is one of the most controversial and emotional issues facing those involved with the industrial relations system. However, a paucity of research has been done on the actual use of replacement workers and how that affects industrial relations outcomes, such as strike activity. Initial research suggests that the use of replacements is associated with longer strikes, supporting the con tention that the use of replacements should be prohibited. Using four case studies, we explore some of the dynamics of strikes that utilize replacements versus those that do not. The results suggest that, in ad dition to economic factors, social and psychological variables may be intricately linked to the relationship between the use of replacements and strike activity.